Effect of inoculum and substrate/inoculum ratio on the performance and methanogenic archaeal community structure in solid state anaerobic co-digestion of tomato residues with dairy manure and corn stover. (November 2018) - Li, Yangyang; Wang, Yanqin; Yu, Zihan; Lu, Jiaxin; Li, Danyang; Wang, Guoying; Li, Yu; Wu, Yue; Li, Shuyan; Xu, Fuqing; Li, Guoxue; Gong, Xiaoyan
Highlights: Effect of L-AD effluent, WAS, and AGS as inoculum on microbial community was studied. L-AD effluent provided sufficient microbes and buffering capacity to reactors at S/I ratio of 6. Methanosaetaceae was the dominant methanogens when inoculated L-AD effluent and WAS. Methanosaetaceae and Methanobacteriaceae were the dominant when inoculated AGS. L-AD effluent was the most suitable inoculum for the fast and successful startup of SS-AD. Abstract: Effects of methanogenic community of inoculum (liquid anaerobic digestion effluent (L-AD effluent), waste activated sludge (WAS), and anaerobic granular sludge (AGS)) and substrate/inoculum ratio (S/I) on reactor performance in solid state anaerobic digestion (SS-AD) were investigated. L-AD effluent, which can provide sufficient microbes and enough buffering capacity to the reactor at an S/I ratio of 6, was found to quickly initiate SS-AD processes. The highest methane production was obtained in reactor inoculated with WAS at an S/I ratio of 2. Higher volatile fatty acids and total ammonia nitrogen concentrations were found when AGS was used as inoculum, which led to a low methane production. Methanosaetaceae, Methanosaetaceae, and Methanosaetaceae together with Methanobacteriaceae were the dominant methanogens in reactors inoculated with L-AD effluent, WAS, and AGS, respectively. These findings suggest among the three inoculum, L-AD effluent is the most effective inoculum for SS-AD of on farm organic waste.